"Red Carbon": A Rediscovered Covalent Crystalline Semiconductor. Issue 40 (3rd September 2022) - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al.
Abstract: Carbon suboxide (C3 O2 ) is a unique molecule able to polymerize spontaneously into highly conjugated light‐absorbing structures at temperatures as low as 0 °C. Despite obvious advantages, little is known about the nature and the functional properties of this carbonaceous material. In this work, the aim is to bring "red carbon, " a forgotten polymeric semiconductor, back to the community's attention. A solution polymerization process is adapted to simplify the synthesis and control the structure. This allows one to obtain this crystalline covalent material at low temperatures. Both spectroscopic and elemental analyses support the chemical structure represented as conjugated ladder polypyrone ribbons. Density functional theory calculations suggest a crystalline structure of AB stacks of polypyrone ribbons and identify the material as a direct bandgap semiconductor with a medium bandgap that is further confirmed by optical analysis. The material shows promising photocatalytic performance using blue light. Moreover, the simple condensation–aromatization route described here allows the straightforward fabrication of conjugated ladder polymers and can be inspiring for the synthesis of carbonaceous materials at low temperatures in general. Abstract : Carbon suboxide is a molecule spontaneously polymerizing into conjugated ladder oligomers composed of carbon and oxygen atoms only, and named "red carbon." Herein, this partially forgotten chemistry is brought back to the attention of the community of covalent semiconductors. As‐synthesized red carbon generates superoxide species upon light irradiation, acting as an efficient photocatalyst, with performance superior to the state‐of‐the‐art carbon nitrides.